THE ROLE OF INTEREST RATES AND PROVINCIAL MONETARY AGGREGATE IN MAINTAINING REGIONAL INFLATION IN INDONESIA - Chandra Utama; Miryam Lilian Wijaya; Charvin Kusuma (Research Report - Humanities and Social Science, 2015)
In most countries, monetary policies are implemented in order to maintain economic stability. The policy may employ interest rate or money supply to derive the assigned national inflation target. Most studies investigate the relationship between monetary policy and inflation use national data. Based on the idea that inflation is a regional phenomenon, the application of provincial data might be more appropriate explaining the relationship between monetary policy and inflation. The study elaborate the impact of changes in provincial money supply, BI Rate (interest rates of central bank), and PUAB (money market interest rates) to regional inflation in the framework Hybrid New Keynesian Phillips Curve (HNKPC). The study employs Generalized Method of Moments (GMM) techniques on panel data of 32 provinces from 2005-III to 2014-IV. The data is classified into 4 groups, which are Jawa-Bali (W1), Sumatera (W2), Kalimantan-Sulawesi (W3), and Papua-Maluku-Nusa Tenggara (W4). The estimation result shows that provincial monetary aggregate influence inflation significantly only in Sumatera. Furthermore, inflation is also effect by BI Rate in Sumatera and Kalimantan-Sulawesi. The study also found that PUAB is significantly affecting inflation in almost all Indonesian regions, except Kalimantan-Sulawesi. This study concludes that interest rates, BI rate and PUAB, is more appropriate than change in provincial money supply to control provincial inflation.Keywords: monetary policy, regional inflation, hybrid NKPCJEL Classification Numbers: E31, E52, R19